Protection and controlled release of vitamin C by different micro/nanocarriers. Issue 12 (22nd April 2022) - Comunian, T.; Babazadeh, A.; Rehman, A.; Shaddel, R.; Akbari-Alavijeh, S.; Boostani, S.; Jafari, S.M.
Abstract: Ascorbic acid, known as vitamin C, is an important antioxidant and food ingredient, and highly sensitive to environmental conditions, which makes its incorporation into food, cosmetic and pharmaceutical products more difficult. The evaluation of its nano/microencapsulation enables the improvement of its stability and controlled release. There are various investigations regarding ascorbic acid encapsulation; however, a deep study related to the scale-up of encapsulation process, its application into food products and digestibility study are still needed. This review highlights the main physicochemical and health properties of vitamin C, recent advances of its encapsulation into micro/nanocarriers, and application in food products. Also, the controlled release and bioavailability of encapsulated forms within different carriers is underlined. The results of published studies clearly show that vitamin C can be successfully protected within micro/nanoencapsulation systems and it can be applied as an efficient ingredient in the formulation of various food products such as bakery goods. Graphical Abstract: UF0001 Different carriers used for the delivery of vitamin C; a: nanoliposomes, b: solid lipid nanoparticles (SLNs), c: nanostructured lipid carriers (NLCs), d: chitosan nanoparticles, e: cyclodextrin nanosponges